A COMPARATIVE ANALYSIS OF CONTEMPORARY SOCIOLINGUISTIC ISSUES IN UZBEK AND ENGLISH - Kasimova Shokhida Shokir qizi (Prospects for innovative technologies in science and education, 2026)
Sociolinguistics, Uzbek, English, globalization, code-switching, identity, multilingualism, digital communication, language policy.